2021
DOI: 10.3332/ecancer.2021.1190
|View full text |Cite
|
Sign up to set email alerts
|

A review of breast cancer pathology reports in Nigeria

Abstract: Background Diagnosis and treatment of cancer rely heavily on imaging, histopathology and molecular information. Incomplete or missing tumour information can hinder the delivery of high-quality care in oncology practice, especially in resource-limited countries. To evaluate the completeness of histopathology reporting in a real-world setting and identify areas for future cancer care delivery research efforts, we retrospectively analysed reports from patients diagnosed with breast cancer who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
0
1
Order By: Relevance
“…Bilaterality (0.4%) was rare in this study similar to that reported by Yesufe et al [7], where they reported a frequency of 0.2% of bilateral tumors. Male breast cancers were reported in 1% of the cases, which was similar to studies done by Adedayo et al (0.7%) [9], Yesufe et al (4.1%) [7] and Maturi et al (0.89%) [8]. The left side breast cancers were slightly more frequent in our population, whereas right sided breast carcinomas are more commonly reported in a study by Yesufe et al [7].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Bilaterality (0.4%) was rare in this study similar to that reported by Yesufe et al [7], where they reported a frequency of 0.2% of bilateral tumors. Male breast cancers were reported in 1% of the cases, which was similar to studies done by Adedayo et al (0.7%) [9], Yesufe et al (4.1%) [7] and Maturi et al (0.89%) [8]. The left side breast cancers were slightly more frequent in our population, whereas right sided breast carcinomas are more commonly reported in a study by Yesufe et al [7].…”
Section: Discussionsupporting
confidence: 90%
“…The audited reports show overall completeness of the report to be 87% , which is higher than the studies by Atanda et al [11], Adedayo et al [9], Kricker et al [12], Yesufe et al [7] and Toma et al [13] where the overall report completeness for the essential parameters was 2.2%, 6.1%, 21%, 61.6% and 74.3% respectively. This could probably be explained by the fact that we have used synoptic-like format for reporting, which resulted in less chances of omission of core elements.…”
Section: Discussioncontrasting
confidence: 51%